Unidentified angular recurrent ulceration responsive to antiviral therapy - Rahmi Amtha; Siti Aliyah Pradono (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Recurrent ulcer on angular area is usually called stomatitis angularis. It is caused by many factors such as vertical dimension reduce, vitamin B12, and immune system deficiency, C. albicans and staphylococcus involvement. Clinically is characterized by painful fissure with erythematous base without fever. Purpose: to describe an unidentified angular ulcer proceeded by recurrent ulcers with no response of topical therapy. Case: An 18-years old male came to Oral Medicine clinic in RSCM who complained of angular recurrent ulcers since 3 years ago which developed on skin and bleed easily on mouth opening. Patient had fever before the onset of ulcers. Large, painful, irregular ulcers covered by red crustae on angular area bilaterally. Patient has been treated with various drugs without improvement and lead to mouth opening limitation. Intra oral shows herpetiformtype of ulcer and swollen of gingival. Case management: Provisional diagnosis was established as viral infection thus acyclovir 200 mg five times daily for two weeks and topical anti inflammation gel were administered. Blood test for IgG/IgM of HSV1 and HSV2 were non reactive, however ulceration showed a remarkable improvement. The ulcers healed completely after next 2 weeks with acyclovir. Conclusion: The angular ulceration on above patient failed to fulfill the criteria of stomatitis angularis or herpes labialis lesion. However it showed a good response to antiviral. Therefore, unidentified angular ulceration was appointed, as the lesion might be triggered by other type of human herpes virus or types of virus that response to acyclovir.Latar belakang: ulser rekuren pada sudut mulut biasanya disebut stomatitis angularis. Kelainan ini disebabkan oleh banyak faktor seperti berkurangnya dimensi vertikal, defisiensi vitamin B12 dan sistem kekebalan tubuh, infeksi C. albicans serta staphylococcus. Secara klinis kelainan ini ditandai dengan fisur sakit pada sudut mulut dengan dasar eritematus tanpa disertai demam. Tujuan: Melaporkan kasus ulser sudut mulut rekuren yang tidak biasa, tanpa respon terhadap terapi topikal yang biasa diberikan. Kasus: Seorang lakilaki berusia 18 tahun datang ke klinik Penyakit Mulut RSCM dengan keluhan ulser rekuren pada sudut mulut yang meluas ke kulit sekitarnya sejak 3 tahun yang lalu. Ulser mudah berdarah saat pasien membuka mulut dan demam sebelum lesi timbul. Ulser membesar, bilateral, sakit, tepi tidak teratur, ditutupi oleh krusta merah. Pasien telah diobati dengan berbagai obat, namun tidak menunjukkan perbaikan. Intra oral tampak ulser jenis herpetiformis pada gingiva disertai dengan pembengkakan. Tatalaksana kasus: Diagnosis awal ditegakkan sebagai infeksi virus, oleh karena itu pasien diberikan acyclovir 200 mg lima kali sehari selama dua minggu dan gel anti radang topikal. Walaupun hasil darah IgG/IgM HSV1 dan HSV2 non reaktif, namun ulserasi menunjukkan penyembuhan yang luar biasa dengan anti virus yang diberikan. Ulser sembuh sempurna setelah pemakaian acyclovir 2 minggu berikutnya. Kesimpulan: ulserasi sudut mulut pada pasien di atas gagal memenuhi kriteria stomatitis angularis atau herpes labialis. Namun ulser menunjukkan respon yang amat baik terhadap antivirus. Diagnosis ditetapkan sebagai ulserasi sudut mulut yang tidak teridentifikasi. Kemungkinan lesi dipicu oleh virus herpes manusia jenis lain atau jenis virus yang memberikan respon terhadap asiklovir.